2017
DOI: 10.1016/j.ecoleng.2016.12.030
|View full text |Cite
|
Sign up to set email alerts
|

Vegetation-wave interactions in salt marshes under storm surge conditions

Abstract: Highlights-Salt marsh vegetation can reduce near-bed orbital velocities during storm surges-Vegetation effect on orbital velocities varies with biophysical properties-Flexible low-growing plant canopies show high resilience to storm surge conditions-More rigid and tall grasses experience stem folding and breakage-The contribution of vegetation to wave dissipation is plant species specific

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
90
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(91 citation statements)
references
References 65 publications
1
90
0
Order By: Relevance
“…For instance, Maza et al () and Bradley and Houser () found that smaller waves were more attenuated for similar water depths when interacting with Puccinela maritima and Thalassia testudinum . Later, Rupprecht et al () demonstrated that orbital velocities and water depths played an important role on the bending angle, and therefore in the frontal area resisting the flow. More flexible stems might be bent by high orbital velocities, extending them in the flow direction, and therefore reducing the actual length that is affecting the flow (Losada et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Maza et al () and Bradley and Houser () found that smaller waves were more attenuated for similar water depths when interacting with Puccinela maritima and Thalassia testudinum . Later, Rupprecht et al () demonstrated that orbital velocities and water depths played an important role on the bending angle, and therefore in the frontal area resisting the flow. More flexible stems might be bent by high orbital velocities, extending them in the flow direction, and therefore reducing the actual length that is affecting the flow (Losada et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…However, to avoid an overestimation of the wave height reduction for relatively long foreshores, the processes wind input (due to Snyder et al (1981)) and whitecapping (due to Komen et al (1984)) are added. All these model descriptions correspond with the implementations in the spectral wave model SWAN (Booij et al, 1999).If the wave-induced bending stresses exceed the plant's flexural strength, the stem will fold or break near the bottom (Rupprecht et al, 2017). The stem breakage model developed in Vuik et al (2018) is implemented in the model framework of Fig.…”
Section: Modeling Of Foreshore Effectsmentioning
confidence: 99%
“…The dynamic motion of vegetation changes the flow and produces eddies which, in turn, alter the flow forcing on the blade and blade motion. The blade motion due to flexibility reduces the relative velocity between flow and vegetation as well as the frontal area, resulting in a reduced drag that decreases velocity attenuation and wave attenuation in the vegetation meadow (Abdolahpour et al, 2018;Bouma et al, 2005;Houser et al, 2015;Mullarney & Henderson, 2010;Paul et al, 2012;Riffe et al, 2011;Rupprecht et al, 2017;Zeller et al, 2014). Numerical models have been developed to solve a force balance equation for the vegetation motion, considering gravity, buoyancy, structural damping, bending stiffness as restoring forces, as well as drag and inertia as driving forces (Ikeda et al, 2001;Leclercq & de Langre, 2018;Luhar & Nepf, 2016;Zeller et al, 2014;Zhu & Chen, 2015).…”
Section: Introductionmentioning
confidence: 99%